Analisis Konsep Teori Produksi Dalam Perspektif Ibnu Khaldun Dan Abdul Manan - Hidayatullah, Muhammad Haris (Jurnal Ilmiah Ekonomi Islam, 2023)
The theory of production is a way to achieve individual and group welfare according to the views of the two figures discussed in this study. This means that the role of production cannot be separated from or supported by the workforce and the organization or group itself. This study aims to find out what the thoughts of Ibnu Khaldun and Muhammad Abdul Manan are regarding the theory of production, especially in the aspects of labor and organization. This research was appointed because researchers so far have not found a comparison of the thoughts of the two figures. This research method uses literature review using primary and secondary data. The results of this study found that the similarity of this thinking is that Ibn Khaldun and Abdul Manan have a goal of achieving prosperity for society. The difference that is obtained is where it is related to labor and organizational issues here. Ibnu Khaldun in the three production groups, he always relates it to work specialization as well as in the intended organization, while Manan in the organization is more directed to how to establish an investment that is in accordance with Islamic law according to Islamic law. vision and mission of the organization.